1991
DOI: 10.1017/s0022029900033471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of liner design on mouthpiece chamber vacuum during milking

Abstract: SummaryThree types of liner (wide bore tapered, wide bore and narrow bore) were compared in a change-over design experiment comprising three 3-d periods and using six lactating Holstein Friesian cows with a wide range in milk flow rate and teat dimensions. Vacuum levels measured within the liner showed a characteristic pattern of three distinct phases: 1, a mouthpiece chamber (MPC) vacuum that fluctuated with vacuum beneath the teat; 2, a stable MPC vacuum that coincided with the period of peak milk flow and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
2
5
0
3
Order By: Relevance
“…High MPC vacuum increases the risk of mastitis (Rasmussen, 1997). Rasmussen et al (1998) observed higher frequency of discoloured teats, and Newman et al (1991) observed circular rings in the teat base associated with high MPC vacuum. The teat tissue is more susceptible to being drawn into the mouthpiece chamber when the vacuum level is high, and blood and lymph may accumulate in the teat tissue and close the milk passage between the udder and the teat, leading to reduced milk flow rate and cow discomfort (Rasmussen, 1997).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…High MPC vacuum increases the risk of mastitis (Rasmussen, 1997). Rasmussen et al (1998) observed higher frequency of discoloured teats, and Newman et al (1991) observed circular rings in the teat base associated with high MPC vacuum. The teat tissue is more susceptible to being drawn into the mouthpiece chamber when the vacuum level is high, and blood and lymph may accumulate in the teat tissue and close the milk passage between the udder and the teat, leading to reduced milk flow rate and cow discomfort (Rasmussen, 1997).…”
mentioning
confidence: 94%
“…The teat tissue is more susceptible to being drawn into the mouthpiece chamber when the vacuum level is high, and blood and lymph may accumulate in the teat tissue and close the milk passage between the udder and the teat, leading to reduced milk flow rate and cow discomfort (Rasmussen, 1997). Newman et al (1991) observed that cows that appeared agitated or kicked at the cluster towards the end of milking were all milked with MPC vacuum exceeding 23 kPa.…”
mentioning
confidence: 99%
“…Ein Beispiel hierfür stellt die Ringbildung und Einschnürung an der Zitzenbasis dar. Newman et al (28) stellten beim Einsatz verschiedenartiger Zitzengummis fest, dass sich bei denjenigen, die im Schaftbereich relativ zur Zitze weit sind bzw. eine weite Bohrung zum kurzen Milchschlauch hin aufweisen, ein hohes Vakuum im Kopfbereich des Zitzengummis aufbaut.…”
Section: Akute Zitzenkonditionsstörungenunclassified
“…Newman et. al (27) Treten die oben beschriebenen Zirkulationsstörungen immer wieder auf, können sie durch die Bildung von Bindegewebe zu chronischen Gewebeveränderungen, wie verhärteten Zitzenspitzen und Einengung des Zitzenkanals, führen. Hieraus resultieren wiederum eine verminderte Milchflussrate und Schwermelkbarkeit (41).…”
Section: Kongestionen Und Zitzenödemeunclassified
“…Vor allem bei Zitzengummis, die im Schaftbereich relativ zur Zitze zu weit sind oder eine weite Bohrung zum kurzen Milchschlauch hin aufweisen (27), lässt sich während des Melkens die Ausbildung eines hohen Vakuums im Bereich des Kopfstücks beobachten. Dadurch wird die Zitze beim Melken in den Melkbecher gesogen, sodass ein Ringwulst entstehen kann (ǠAbb.…”
Section: Ringbildung Und Einschnürungen An Der Zitzenbasisunclassified